A novel Ca2+-signal transduction inhibitor, Kujione A, isolated from medium polar fractions of Kuji amber. (August 2020) - Abe, Junpei; Koshino, Hiroyuki; Shimoda, Nozomu; Kimura, Ken-ichi
Graphical abstract: Highlights: A new clerodane derivative, named kujione A was isolated from the methanol extract of Kuji amber. The structure was elucidated as 15-nor-2-oxo-3-cleroden-13-ol. It is categorized a different type of compound which has not been found previously in isolated constituents from Kuji amber. It has growth-restoring against mutant yeast and no activity against the degranulation of RBL-2H3 cells. Abstract: Five new and one unsual known bioactive compounds have been isolated from the methanol extract of Kuji amber which was subjected to silica gel column chromatography in order to yield lipophilic compounds. A new clerodane derivative, named Kujione A (15-nor-2-oxo-3-cleroden-13-ol), was isolated from the medium polar fractions. This was done using Kujione A's growth-restoring activity against a mutant Saccharomyces cerevisiae strain ( zds1 Δ erg3 Δ pdr1/3 Δ) that is hypersensitive with respect to Ca² + -signal transduction. The structure was elucidated by spectroscopic data, HREIMS, along with 1D- and 2D-NMR, among others. 15-norclerodane has been categorized as a new and distinct compound because it has a conjugated carbonyl functional group; it has not been found in isolated constituents from Kuji amber.